Classical Rhetoric in the Middle Ages : The Medieval Rhetors and Their Art 400-1300, with Manuscript Survey to 1500 CE - Ward, John O., 1940- (International Studies in the History of Rhetoric, 2018)
Classical Rhetoric in the Middle Ages: The Medieval Rhetors and Their Art 400-1300, with manuscript survey to 1500 CE is a completely updated version of John Ward's much-used doctoral thesis of 1972, and is the definitive treatment of this fundamental aspect of medieval and rhetorical culture. It is commonly believed that medieval writers were interested only in Christian truth, not in Graeco-Roman methods of 'persuasion' to whatever viewpoint the speaker / writer wanted. Dr Ward, however, investigates the content of well over one thousand medieval manuscripts and shows that medieval writers were fully conscious of and much dependent upon Graeco-Roman rhetorical methods of persuasion. The volume then demonstrates why and to what purpose this use of classical rhetoric took place.